Menggagas Pengembangan Lingkungan Pembelajaran Ubikuitus sebagai Proyeksi Lingkungan Ubikuitus di Korea Selatan - Wirawan Yogiyatno (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
Indonesia's Internet users mostly are high school students. This is an opportunity for education activists to provide learning system that can be accessed anytime and anywhere just similar to regular websites on Internet. Learning environment that is accessible anytime and anywhere is built based on ubiquitous computing. Republic of Korea is a country that has a program to develop ubiquitous city, which one of its service is ubiquitous learning environment. In this study, a literature study about ubiquitous computing, ubiquitous learning environment, its characterics and components, also its possibility to implement on Indonesian schools was conducted. This study shows that ubiquitous learning environment development, with its components are a server providing learning management system software, hotspot access points, smartphones that have an application installed to access the learning management system, and radio frequency identification system, can be done in any education unit that has supporting factors for those components.